2016
DOI: 10.1016/j.spa.2015.11.010
|View full text |Cite
|
Sign up to set email alerts
|

The α-hypergeometric stochastic volatility model

Abstract: The aim of this work is to introduce a new stochastic volatility model for equity derivatives. To overcome some of the well-known problems of the Heston model, and more generally of the affine models, we define a new specification for the dynamics of the stock and its volatility. Within this framework we develop all the key elements to perform the pricing of vanilla European options as well as of volatility derivatives. We clarify the conditions under which the stock price is a martingale and illustrate how th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…In this section we will tackle the problem of pricing barrier options under the 2-hypergeometric stochastic volatility -a particular case of the α-hypergeometric stochastic volatility model which was defined by Da Fonseca and Martini [1] as follows:…”
Section: An Asymptotic Expansion Approach To Barrier Option Pricingmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section we will tackle the problem of pricing barrier options under the 2-hypergeometric stochastic volatility -a particular case of the α-hypergeometric stochastic volatility model which was defined by Da Fonseca and Martini [1] as follows:…”
Section: An Asymptotic Expansion Approach To Barrier Option Pricingmentioning
confidence: 99%
“…Like Da Fonseca and Martini [1], we assume that the model is given directly under a risk-neutral measure Q. The deterministic function r(t) represents the (possibly time-dependent) interest rate, while the parameters a and c can be used to set the market price of volatility risk.…”
Section: An Asymptotic Expansion Approach To Barrier Option Pricingmentioning
confidence: 99%
See 1 more Smart Citation
“…In chapter 4, we develop an approximate pricing formula for the European option under the Hypergeometric stochastic volatility model introduced in [DM16] to address the shortcomings associated with pricing option using the Heston stochastic volatility model. We assume that the asset price S t and volatility V t at time t is governed by the following dynamics:…”
Section: Chapter 1 Introduction and Main Resultsmentioning
confidence: 99%
“…It has long been observed that the volatility of a derivatives cannot be a constant but varies with the time to maturity and strike, as such for a more accurate modeling of the asset prices in financial markets, stochastic volatility models are introduced. [DM16], the α-Hypergeometric stochastic volatility model is introduced to ensure that the stochastic volatility is strictly positive. For an asset, the asset price S t and volatility V t at time t is governed by the following dynamics:…”
Section: Introductionmentioning
confidence: 99%